Targeted Delivery of Mycobacterial Antigens to Human Dendritic Cells via Siglec-7 Induces Robust T Cell Activation - Norihito Kawasaki; Cory D. Rillahan; Tan‐Yun Cheng; Ildiko Van Rhijn; Matthew S. Macauley; D. Branch Moody; James C. Paulson (2014)
Lipids from mycobacteria can be presented to human T cells by group 1 CD1 Ag-presenting molecules (CD1a, CD1b, and CD1c). Group 1 CD1-restricted T cells are activated by lipid Ags presented by myeloid dendritic cells (DCs), after which they generate antibacterial effector functions, including IFN-γ secretion and cytolysis. Thus, mycobacterial lipids are being investigated as components of novel vaccines for mycobacterial infections. In this study we show that the mycobacterial lipid Ag C80 glucose-6-monomycolate can be delivered to human CD1b(+) DCs via targeted liposomal nanoparticles, leading to robust group 1 CD1-restricted activation of T cells. Targeting was achieved by decorating the liposomes with a high-affinity glycan ligand of sialic acid-binding Ig-like lectin (Siglec)-7, a siglec receptor expressed on DCs that mediates rapid endocytosis and transport of its cargo to lysosomes. An Ab to Siglec-7 completely blocked the binding of targeted liposomes to human monocyte-derived DCs (Mo-DCs), demonstrating their targeting specificity. Mo-DCs pulsed with targeted liposomes containing C80 glucose-6-monomycolate more potently activated a CD1b-restricted T cell line relative to Mo-DCs pulsed with free lipid Ag or antigenic liposomes without Siglec-7 ligand. These data suggest that the endocytic function of Siglec-7 can be exploited to deliver glycolipid Ags to their target cell and increase the efficiency of display to T cells.